If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7-3x=3=8x
We move all terms to the left:
7-3x-(3)=0
We add all the numbers together, and all the variables
-3x+4=0
We move all terms containing x to the left, all other terms to the right
-3x=-4
x=-4/-3
x=1+1/3
| 18+3x+5x-6•2=2x+6 | | -2x-5(2x-3)=19 | | (2x+21)-5x=0 | | 12+7x-21=-8(3-x)4x | | 5x+3’=2x-3 | | 2x=60+5× | | 7x+156=9x184 | | V=4/3x3.14x64 | | 5b+12=(b+6) | | -3/10+a=2/55 | | -8=x-(-15) | | 3(n-6)=7-5(n-3) | | 2x^2+15=x | | 1⁄2n·=3 | | 5b^2-20=-11b | | 29-n=4(n-2) | | 1/8x/5=25 | | 2(2x+5)=2x+7 | | 2x+3x=34 | | 2x+20=60,x | | 2x+12=x6 | | 2x-4=-9=x | | 5x-3=-4x+24 | | 4(x+3)=4x+5 | | 1/4v=2.5 | | w=w+5 | | w=3(w-2) | | 81-61x=12x+15 | | 1-9x=-89 | | 6+-3x=-54 | | x2+10x+25=8 | | 6k^2−8=0 |